Evaluation Learning Sociology With CIPP Approach at SMAN 6 PALU - Ifmawati, Elvia Nur; Latief, Juraid Abd; Hasdin; Suyuti (Kirana Publisher (KNPub), 2025)
Research result show that in terms of context, learning Sociology at SMAN 6 Palu is relevant and appropriate need students , vision and mission schools , and the 2013 curriculum . This is looks from teaching materials taught in accordance competence , condition students , and problems that occur in society. input aspects , qualifications Academic and professionalism of Sociology teachers fulfil standards , facilities and infrastructure available enough , and learning media used in a way creative , though Still happen obstacle technology and accessibility.From process aspect , planning learning arranged based on the relevant RPP , its implementation walk in a way creative and humane , and it happens active interaction​ between students and teachers. Discussion method , ask questions answer , and use of media also support creation living and meaningful learning . Obstacles occur in the aspect evaluation , namely limitations time and problems technicalities that sometimes interfere with the assessment process learning. Meanwhile, in the product aspect , learning Sociology at SMAN 6 Palu achieved sufficient results​ maximum . This is seen in aspect cognitive , attitudes , and skills students who demonstrate improvement . Students more understand material , capable analyze problem Social , and active look for solution on problems that occur in society. Based on findings said , it was concluded that learning Sociology at SMAN 6 Palu is underway Enough good and appropriate needs , but Still need improvements in the process aspects , media usage , and evaluation in order to achieve objective maximum learning . Researchers​ recommend the need repair planning , approach learning , and more media use creative , contextual , and humane , in order to support achievement vision , mission and goals learning Sociology at SMAN 6 Palu.